Dinamika Pohon Mahoni (Swietenia Macrophylla King) Pada Agroforestry Pola Lorong (Alley Cropping) - Moch. Sambas Sabarnurdin; Priyono Suryanto; W. B. AryonoSury (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2004)
-